The role of PKK television channels in spreading national awareness. It is a field research for both STERK.TV and TV.RONAHI. - Hawre Mahmood Rasool; Zhilwan Abdullah Ahmed (The Scientific Journal of Cihan University– Sulaimaniya, 2025)
This research has been conducted in light of both methods of (Historical and Description) which have been carried out through the regulation Survey & Description methods, on a group of people of Sulaimanya City on both satellite channels, (STREK TV) and (RONAHI TV), which are run by PKK. These two channels taken as sample among others that are belong to this party. The fundamental outcome of this research can be seen in identifying the role of satellite TV channels of PKK in creating affiliation spirit towards the nation in the heart of Kurds- in addition to explaining their role in historical background of Kurdish nation in all its historical stages. In the other hand information on the role of these TV channels of the political party in directing people of Kurdistan in order to work on national demands such as; (autonomy, federalism, confederation, self-determination, Kurdish statehood), besides one of the goals of this research is, knowledge on the capacity of these Channels in establishing connection between Kurdish community in abroad and Kurdish people in Kurdistan This research has been achieved some specific results; the most important are: Within attitude of %58.7 of the research sample, the researchers came to conclusion that both channels RONAHI and STREK TV have critical role in taking Kurdish national history into account, explaining its stages, enlighten global national concepts. Within negative responses of %63 of participants in the survey the researchers realized that both TV channels RONAHI and STREK have negative and weak roles in directing people of Kurdistan to achieving the national demands such as; (autonomy, federalism, confederation, self-determination, Kurdish statehood). Both TV channels RONAHI and STREK have a great role In creating and deepening affiliation spirit among Kurdish individuals based on conclusion of researchers.